THE NICHE TOURISM DEVELOPMENT OF ONE OF THE MOST MYSTERIOUS FORESTS IN ROMANIA: THE HOIA-BACIU FOREST - Marius-George OPREA; Marius-Cristin LAZIN; Elena-Cristina MARTIUC (Territorial Identity and Development, 2016)

(untitled)
During the last few years, the Hoia-Baciu Forest, located near Cluj-Napoca, in Transylvania, Romania, has started to attract the attention of the local community after being included in diverse TOPs of the most haunted and creepiest places in the world, alongside other areas with similar phenomena. It became famous in 1968, when several people captured on a camera a flying object which was categorised by the professionals as UFO. Hoia-Baciu continues to fascinate and we want to emphasise its profile: is it a tourist destination yet or just a popular forest among locals, for picnics or other leisure activities? What should be done to transform it in a niche tourism destination? In order to find out, we analysed the data of the Hoia-Baciu Project, designed (by the local Romania –Your Lifetime Experience NGO) to include this mystical forest in the tourist circuit: tourist demands (06.2014-06.2016), activities for locals (2014-2016) and the results of a photo contest meant to answer to the question “what does the Hoia-Baciu Forest mean to me?” (2016). We also analysed the demands for the Hoia-Baciu Forest at Cluj-Napoca Tourist Information Center, in comparison to the total demands and the number of tourist arrivals in Cluj-Napoca. We answered why the Hoia-Baciu Forest is a niche destination for dark and paranormal tourism (among tourists) and just an ordinary attraction for locals.